Preclinical reserpine models recapitulating motor and non-motor features of Parkinson’s disease: Roles of epigenetic upregulation of alpha-synuclein and autophagy impairment - Li, Yang; Yin, Qiao; Wang, Bing; Shen, Tingting; Luo, Weifeng; Liu, Tong (Frontiers in Pharmacology, 2022)
Reserpine is an effective drug for the clinical treatment of hypertension. It also induces Parkinson's disease (PD)-like symptoms in humans and animals possible through the inhibition of monoamine vesicular transporters, thus decreasing the levels of monoamine neurotransmitters in the brain. However, the precise mechanisms remain unclear. Herein, we aimed to develop a preclinical reserpine model recapitulating the non-motor and motor symptoms of PD and investigate the underlying potential cellular mechanisms. Incubation of reserpine induced apoptosis, led to the accumulation of intracellular reactive oxygen species (ROS), lowered DNA methylation of alpha-synuclein gene, resulted in alpha-synuclein protein deposition, and elevated the ratio of LC3-II/LC3-Ⅰ and p62 in cultured SH-SY5Y cells. Feeding reserpine dose-dependently shortened the lifespan and caused impairment of motor functions in male and female Drosophila. Moreover, long-term oral administration of reserpine led to multiple motor and non-motor symptoms, including constipation, pain hypersensitivity, olfactory impairment, and depression-like behaviors in mice. The mechanistic studies showed that chronic reserpine exposure caused hypomethylation of the alpha-synuclein gene and up-regulated its expression and elevated the ratio of LC3-II/LC3-Ⅰ and expression of p62 in the substantia nigra of mice. Thus, we established preclinical animal models using reserpine to recapitulate the motor and non-motor symptoms of PD. Chronic reserpine exposure epigenetically elevated the levels of alpha-synuclein expression possible by lowering the DNA methylation status and inducing autophagic impairment in vitro and in vivo.